MODEL PERUBAHAN SERAPAN MINYAK PADA KENTANG SELAMA PENGGORENGAN - Rina Pratiwi Pudja, Ida Ayu (Agrotekno; Vol. 13, No. 1 Februari 2007)
Frying  is  one  of  fast  and  practical  of  cooking  process of food using fat or oil media. The aims of the research were to find out, test and  apply the  model  of  oil absorption  in potatoes during  frying .  Frying  temperatures  was  adjusted  at  1400C, 1600C  and  1800C,  with  interval  time  to  analysis  at  0,  30,  90, 150,  300, dan  600  second. Fresh  potatoes  were  cut  in  cylinder shaped  with  diameter  of  0,9  cm  and  4  cm  long.  The  result showed that the higher frying temperature, the higher absorption of  fat  during  frying.  The  rate  of  fat  absorption  could  be analogically  expressed  as  the  Newton  model  for  cooling,  to prediction  absorption  of  fat  during  frying  in  fresh  potatoes  in other temperature.
Keywords: Oil content, potatoes, frying.